2016
DOI: 10.1007/978-3-319-47217-1_17
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Selection Hyper-heuristics on the Extended HyFlex Domains

Abstract: Abstract. Selection hyper-heuristics perform search over the space of heuristics by mixing and controlling a predefined set of low level heuristics for solving computationally hard combinatorial optimisation problems. Being reusable methods, they are expected to be applicable to multiple problem domains, hence performing well in cross-domain search. HyFlex is a general purpose heuristic search API which separates the high level search control from the domain details enabling rapid development and performance c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 13 publications
(26 reference statements)
0
17
0
Order By: Relevance
“…In addition, hyperheuristics [Ochoa et al, 2012] can also be seen as a form of DAC. In this field, it has been shown that dynamic heuristic selection outperforms static approaches on combinatorial optimization problems like Knapsack or Max-Cut [Almutairi et al, 2016].…”
Section: Related Workmentioning
confidence: 99%
“…In addition, hyperheuristics [Ochoa et al, 2012] can also be seen as a form of DAC. In this field, it has been shown that dynamic heuristic selection outperforms static approaches on combinatorial optimization problems like Knapsack or Max-Cut [Almutairi et al, 2016].…”
Section: Related Workmentioning
confidence: 99%
“…Regarding hyperheuristics, several options can be found. HyFlex is a framework that aims to minimize the problem domain knowledge required to implement solvers, allowing us to focus the design effort on the construction of adaptive high‐level algorithms/strategies. This can be addressed by providing a number of problem domain modules, where each one encapsulates the problem‐specific algorithm components.…”
Section: Software Design Support For Heuristic Algorithmsmentioning
confidence: 99%
“…There is an emerging interest in the software design perspective of heuristic methods, including the software design elements within reusable libraries and the study of design patterns for metaheuristics . Several libraries and utilities have been reported in the literature to address software design issues of heuristic algorithms at the metaheuristic level and hyperheuristic level or for generic purposes . These alternatives are commonly constrained to the application of design patterns defined in specific‐purpose conceptual models, eg, evolutionary computation.…”
Section: Introductionmentioning
confidence: 99%
“…Equation (1) is the objective function that calculates the sum of the weights of the objects in packing P. Equation (2) ensures that at most one object from set T j can be packed in packing P.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The characteristics of the test instances are reported in Tables 7 to 9. In these three tables, for each instance, the columns with the headings Var, Cnst, Density, Max_One, and Weight show the number of objects (|I|), number of constraints (|J |), percentage of non-null elements in the constraint matrix, size of the largest set |T j | over all j ∈ {1, 2, ... , M}, and weight c i ∈ [1-1] or [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] of object i ∈ I, respectively. All the test instances can be downloaded from http://www3.inrets.fr/~delorme/Instancesfr.html.…”
Section: Accepted Manuscriptmentioning
confidence: 99%